The Transfer of Persian Language Speech Acts into English Language - Pakzadian, Maryam; Dastjerdi, Hossein Vahid (Mediterranean Journal of Social Sciences, 2012)
This paper investigates socio-pragmatic transfer of speech acts from Persian language into English language. The researchercompares the data gathered from Persian speakers of English and American native English in five different service situations. Persianspeakers of English have different semantic interpretations from native American speakers, they conform to different sociolinguisticnorms. So when Persian speakers want to speak English they consider their own cultural and social norms and transfer them in toEnglish. Misunderstanding and break downs in conversations are due to this socio-pragmatic transfer. Adhering to different speakingrules and models of accepted behavior can cause different cultural perceptions about the L2 speakers, some of which are not trueperceptions of course. So we should be careful about false cultural perceptions naming stereotypes without having knowledge about L2speakers' cultural and social backgrounds.